Comment on Welch's 'Thy Thylacoleo is a thylacine', Australian Archaeology, 80:40–47. Issue 1 (2nd January 2016) - Lewis, Darrell
Abstract: In this paper, I review Welch's critique ( Australian Archaeology 80:40–47) of claims by Akerman, Akerman and Willing and Woodhouse that depictions of Thylacoleo exist in Kimberley rock art. I agree with his conclusion that these claims are unfounded and that the depictions probably represent thylacines. There are, however, problems with the methodology he employs to reach this conclusion, a number of factual mistakes and a failure to adequately acknowledge the work of previous researchers. An appropriate methodology for identifying species in rock art, developed by a number of researchers in the 1970s and 1980s, is outlined.